Smoke and Vapor of Najāsah Between Fiqh and Chemistry: An Analytical Jurisprudential Study - Karakira, Musatafa Muhammad (Journal of Islamic Sciences, 2025)
The research aims to distinguish between smoke and vapor, and to distinguish between the rulings of each in terms of purity and impurity. It also identifies the cases in which impurity is excused, and the methods for removing it. The researcher adopted the deductive-evidential approach and the analytical-explanatory approach, dividing the research into two sections. The first defines the terms of the title, and the second explains the rulings on smoke and vapor. The research concluded with the following key findings: The reality of smoke differs from the reality of vapor, and that smoke is essentially the same as its origin, while vapor is of two types: those that are essentially the same as its origin and those that are not.
Keywords: Impurity; Purity; Smoke; Steam